The Italian Mastocytosis Registry: 6-year experience from a hospital-based registry. (12th September 2018) - Merante, Serena; Ferretti, Virginia V; Elena, Chiara; Brazzelli, Valeria; Zanotti, Roberta; Ner, Iria; Magliacane, Diomira; Belloni Fortina, Anna; Ingeborg, Forer; Pastorello, Elide A; Pieri, Lisa; Papayannidis, Cristina; et al.
Aim: We collected 'real-life' data on the management of patients with mastocytosis in the Italian Mastocytosis Registry.Methods: Six hundred patients diagnosed with mastocytosis between 1974 and 2014 were included from 19 centers.Results: Among adults (n = 401); 156 (38.9%) patients were diagnosed with systemic mastocytosis. In 212 adults, no bone marrow studies were performed resulting in a provisional diagnosis of mastocytosis of the skin. This diagnosis was most frequently established in nonhematologic centers. In total, 182/184 pediatric patients had cutaneous mastocytosis. We confirmed that in the most patients with systemic mastocytosis, serum tryptase levels were >20 ng/ml and KIT D816V was detectable.Conclusion: The Italian Mastocytosis Registry revealed some center-specific approaches for diagnosis and therapy. Epidemiological evidence on this condition is provided.